(untitled) (Journal of the College of Education for Women, 2025)
This study investigates how first language (L1) competence influences the phonological production of English liquid consonants /l/ and /r/ among Mandarin Chinese speakers. The research adopts an experimental acoustic-phonetic design supported by auditory analysis and perceptual judgment to examine pronunciation variation. Four Mandarin-speaking postgraduate learners of English participated in controlled minimal-pair production tasks in isolated and sentence-embedded forms. Guided by Flege’s (1995) Speech Learning Model (SLM), the study analyzed the extent to which L1 phonetic categories affect the acquisition of L2 sound contrasts. Findings show that participants generally produced the /l/ sound accurately, while the /r/ sound exhibited persistent distortions and substitutions due to the absence of a distinct /r/ phoneme in Mandarin. These difficulties increased when sounds appeared in full sentence contexts, indicating heavier phonological processing demands. The results demonstrate a clear influence of L1 interference on segmental accuracy in English pronunciation. The study highlights the necessity of implementing targeted phonological instruction to support Mandarin learners in overcoming persistent difficulties with the /r/ sound.